2013
DOI: 10.1007/s12160-013-9563-x
|View full text |Cite
|
Sign up to set email alerts
|

Pain Hypervigilance is Associated with Greater Clinical Pain Severity and Enhanced Experimental Pain Sensitivity Among Adults with Symptomatic Knee Osteoarthritis

Abstract: Background Pain hypervigilance is an important aspect of the fear-avoidance model of pain that may help explain individual differences in pain sensitivity among persons with knee osteoarthritis (OA). Purpose The purpose of this study was to examine the contribution of pain hypervigilance to clinical pain severity and experimental pain sensitivity in persons with symptomatic knee OA. Methods We analyzed cross-sectional data from 168 adults with symptomatic knee OA. Quantitative sensory testing was used to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 41 publications
(46 reference statements)
1
32
0
Order By: Relevance
“…In addition, subjective health status significantly affected current arthritic pain in subjects with osteoarthritis. Previous studies have reported an association between osteoarthritis and psychosocial factors, such as depression and catastrophizing, 42 , 43 , 44 which supports our study results. Therefore, more attention needs to be paid to psychiatric causes and outcomes of osteoarthritis and arthritis related joint pain.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, subjective health status significantly affected current arthritic pain in subjects with osteoarthritis. Previous studies have reported an association between osteoarthritis and psychosocial factors, such as depression and catastrophizing, 42 , 43 , 44 which supports our study results. Therefore, more attention needs to be paid to psychiatric causes and outcomes of osteoarthritis and arthritis related joint pain.…”
Section: Discussionsupporting
confidence: 92%
“…The detection of thermal stimuli by primary afferents, the transmission of this information to the brain and the subsequent generation of the actual experience of temperature and pain in the individual involves interplay of central and peripheral sensory mechanisms that is not fully understood. It is, however, known that innocuous cold and heat sensation and cold and heat pain are mediated by different peripheral receptors and modulated by several mechanisms, including those driven by comorbidity in the CNS (26)(27)(28)(29)(30). It remains to be determined whether the characteristic QST profile observed in this cohort of patients reflects a common phenotype over-represented in patients with persistent pain or a common pathophysiological process that might be responsive to multimodal pain treatment.…”
Section: Discussionmentioning
confidence: 91%
“…Cognitive changes accompanying chronic pain often involve disproportionate attentional selection of pain and pain-associated information at the expense of the remaining sensory inputs [ 114 – 116 ]. Hypervigilance to pain is associated both with higher sensitivity to experimental pain [ 117 – 118 ] and greater clinical pain in FMS and other conditions [ 117 , 119 ]. Further, there is an emerging view that increased vigilance in people with FMS may not be circumscribed to painful inputs but rather represent a generalized, perceptual style of amplification of a variety of sensory information [ 120 ], including innocuous or auditory inputs [ 121 ].…”
Section: Discussionmentioning
confidence: 99%